PENGEMBANGAN E-KOMIK BERBASIS KOOPERATIF STAD UNTUK MENINGKATKAN PEMAHAMAN KONSEP MATERI IPAS SISWA KELAS IV SD - Putu Intan Asrini; Kadek Yudiana; Dewa Gede Agus Putra Prabawa (STKIP Subang, 2026)
This study aims to develop a valid, practical, and effective STAD-based cooperative e-comic medium to improve the conceptual understanding of science material among fourth-grade students at SD Negeri 1 Penglatan. The research problem stems from students’ low conceptual understanding, teaching that remains teacher-centered, and the use of media that lacks variety and does not yet optimally utilize technology. This study is a research and development (R&D) study using the ADDIE model. The research subjects included 2 content experts, 2 media experts, 2 teachers, and 25 fourth-grade students at SD Negeri 1 Penglatan, with the research object being the STAD-based cooperative e-comic medium. Product validation was conducted by content and media experts, while the practicality test involved teachers and students through individual and small-group tests. Data collection methods included questionnaires and tests with quantitative descriptive analysis. The research results indicate that the e-comic media has a very high level of validity, with a percentage of 96% (subject matter experts) and 95% (media experts). The practicality of the media received an average of 97% from teachers, as well as 94% in individual and small-group tests, categorized as very practical. The results of the effectiveness test showed an increase in the average score from 44.00 on the pretest to 84.20 on the posttest, with a significance value of the paired sample t-test of 0.000 (< 0.05) and an N-Gain value of 0.74 (effective category). Thus, the STAD-based cooperative e-comic medium is deemed valid, practical, and effective for improving students’ understanding of IPAS concepts.